Association of Metatarsalgia After Hallux Valgus Correction With Relative First Metatarsal Length. (June 2016) - Nakagawa, Satoru; Fukushi, Jun-ichi; Nakagawa, Takeshi; Mizu-uchi, Hideki; Iwamoto, Yukihide
Background: Metatarsalgia is frequently associated with hallux valgus. The aim of this study was to evaluate how the relative length and position of the first metatarsal head influenced metatarsalgia and plantar callosities beneath the lesser metatarsal heads. Methods: A retrospective analysis of the clinical data and radiographs of 102 cases was performed at a mean follow-up of 16 months after biplane interlocking osteotomies. Clinical evaluation was made using the Japanese Society for Surgery of the Foot (JSSF) hallux scale. Radiologic evaluation was made with standard weight-bearing anteroposterior radiographs, and the hallux valgus angle (HVA), intermetatarsal 1-2 angle (IMA), distal metatarsal articular angulation (DMAA), and the sesamoid position were evaluated. Relative first metatarsal length (RML) was determined according to Nilsonne/Morton's technique. Results: The mean preoperative HVA decreased from 37 to 3 degrees, and the mean IMA from 17 to 4 degrees. The mean JSSF-hallux score improved from 56 to 96 points. The mean preoperative area of plantar callosities decreased from 3.1 to 1.5 mm 2 . Sixty percent of metatarsalgia cases improved, and 85% of painless callosities disappeared postoperatively. Among radiologic parameters, postoperative RML was most significantly associated with JSSF score ( P < .0001) and the presence of postoperative metatarsalgia ( P < .0001). Receiver operating characteristic analysis revealed that the RML cut-off point was −3 mm for avoiding metatarsalgia, with an area under the curve of 0.88, a specificity of 88%, and a sensitivity of 85%. Conclusion: Preservation of relative first metatarsal length during first metatarsal osteotomy was important to prevent postoperative metatarsalgia. Level of Evidence: Level IV, retrospective case series.